Show that if   `log_b a=c`  and  `log_y b=c`  , then `log_a y=c^-2` .

Asked on by lbawa

1 Answer | Add Yours

hala718's profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

`log_b a = c`

`log_y b = c`

`==> log_a y= c^-2`

We know that: `log_a b= (log_c b)/(log_c a)`

`` `log_a y=( log_b y)/(log_b a)= (log_b y)/C .........(1)`

`log_b y = (log_y y)/(log_y b) = 1/C .........(2)`

Now we will subsitute (2) into (1).

`==gt log_a y= (1/c)/c= 1/c^2 = c^-2 `

`==gt log_a y= c^-2`


We’ve answered 320,051 questions. We can answer yours, too.

Ask a question